Analisis Faktor Penentu Loyalitas Pengguna ShopeePay Pada Generasi Muda Kota Bandung - Mohammad Yudi Indriawan; Farid Arifin (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
The advancement of financial technology in Indonesia has driven the popularity of digital wallets (e-wallets) as transaction methods. ShopeePay, as one of the leading e-wallets, faces challenges in maintaining user loyalty amidst industry competition. This study aims to analyze the influence of perceived service ease and cashback promotions on ShopeePay user loyalty among students of the Faculty of Economics and Business, Universitas Langlangbuana. A quantitative approach was applied with descriptive and verificative methods. A sample of 100 respondents was selected via snowball sampling. Data were collected through questionnaires and analyzed using multiple linear regression (path analysis) with SPSS 26. The results indicate that the perceived ease of ShopeePay service is in the moderately easy category, cashback promotions are moderately attractive, and user loyalty (intention to reuse) falls in the moderately high category. Partial t-tests confirm that both perceived ease and cashback promotion have a positive and significant individual effect on ShopeePay reuse intention. The simultaneous F-test shows that these two variables together have a significant effect on reuse intention (F_calculated = 104.634; p < 0.001). These findings suggest that service ease and cashback promotions are determinant factors of ShopeePay user loyalty. Cashback promotions exhibit a more dominant influence than service ease in encouraging repeated use, implying that loyalty enhancement efforts should emphasize financial incentives without neglecting service simplicity.